FINANCIAL EXPLOITATION: RISK, RECIPROCITY AND NEGOTIATION—AN AFRICAN AMERICAN WOMAN'S CASE. (11th November 2018) - Lysack, C; Luboorsky, M; Hall, L
Abstract: A recognized public health priority, financial exploitation (FE) of the elderly is prevalent, rapidly rising, and leads to dire health and well-being impacts. Currently, a mere fraction of cases is reported to authorities; notably, less than 10% of cases are reported by elderly themselves. Today systematic data on the reasoning and values that explain why so few elderly report FE remain scarce, but has been identified as a barrier to reducing FE and FE-related harms. Using forensic case follow-back and interview methods drawn from an ongoing Detroit study, we report on contextual factors and personal perceptions, reasons and values underlying the (non)reporting decisions of an older African American woman who incurred FE. Content analyses of interviews and case records for this woman yield several key findings: (a) analytic limitations of single episode vs. a process or serial events conception of FE; (b) multiplex moral reasoning; (c) active strategic attempts to negotiate accountability with perpetrators, e.g., banks; (d) paradox of fulfilling personal values by non-reporting, that is, through 'giving' (i.e., generativity); and (e) two-way manipulation between victims and perpetrators of FE, in contrast to stereotypes of elderly as passive victims. Overall, findings of multidimensional features in FE reporting counter current frameworks that under-specify contextual and personal factors in FE reporting by elderly. Challenges to FE research, and implications for current models of FE risk are discussed. [Support: Michigan Health Endowment Fund; American House Foundation, Detroit]